Rapid, high-sensitivity analysis of oxyhalides by non-suppressed ion chromatography-electrospray ionization-mass spectrometry: application to ClO4−, ClO3−, ClO2−, and BrO3− quantification during sunlight/chlorine advanced oxidation. Issue 9 (8th July 2020) - Young, Tessora R.; Cheng, Shi; Li, Wentao; Dodd, Michael C.
Abstract : A novel, non-suppressed ion chromatography-mass spectrometry method enables rapid analysis of all regulated oxyhalides at sub-μg L −1 levels in natural waters and waters subjected to chlorination and sunlight/chlorine advanced oxidation. Abstract : A rapid and sensitive method is described for measuring perchlorate (ClO4 − ), chlorate (ClO3 − ), chlorite (ClO2 − ), bromate (BrO3 − ), and iodate (IO3 − ) ions in natural and treated waters using non-suppressed ion chromatography with electrospray ionization and tandem mass spectrometry (NS-IC-MS/MS). Major benefits of the NS-IC-MS/MS method include a short analysis time (12 minutes), low limits of quantification for BrO3 − (0.10 μg L −1 ), ClO4 − (0.06 μg L −1 ), ClO3 − (0.80 μg L −1 ), and ClO2 − (0.40 μg L −1 ), and compatibility with conventional LC-MS/MS instrumentation. Chromatographic separations were generally performed under isocratic conditions with a Thermo Scientific Dionex AS16 column, using a mobile phase of 20% 1 M aqueous methylamine and 80% acetonitrile. The isocratic method can also be optimized for IO3 − analysis by including a gradient from the isocratic mobile phase to 100% 1 M aqueous methylamine. Four common anions (Cl −, Br −, SO4 2−, and HCO3 − /CO3 2− ), a natural organic matter isolate (Suwannee River NOM), and several real water samples were tested to examine influences of natural water constituents on oxyhalide detection. Only ClO2 − quantification was significantly affected – by elevated chloride concentrations (>2 mM) and NOM. The method was successfully applied to quantify oxyhalides in natural waters, chlorinated tap water, and waters subjected to advanced oxidation by sunlight-driven photolysis of free available chlorine (sunlight/FAC). Sunlight/FAC treatment of NOM-free waters containing 200 μg L −1 Br − resulted in formation of up to 263 ± 35 μg L −1 and 764 ± 54 μg L −1 ClO3 −, and up to 20.1 ± 1.0 μg L −1 and 33.8 ± 1.0 μg L −1 BrO3 − (at pH 6 and 8, respectively). NOM strongly inhibited ClO3 − and BrO3 − formation, likely by scavenging reactive oxygen or halogen species. As prior work shows that the greatest benefits in applying the sunlight/FAC process for purposes of improving disinfection of chlorine-resistant microorganisms are realized in waters with lower DOC levels and higher pH, it may therefore be desirable to limit potential applications to waters containing moderate DOC concentrations ( e.g., ∼1–2 mgC L −1 ), low Br − concentrations ( e.g., <50 μg L −1 ), and circumneutral to moderately alkaline pH ( e.g., pH 7–8) to strike a balance between maximizing microbial inactivation while minimizing formation of oxyhalides and other disinfection byproducts.